Acid mine drainage in the Gauteng province of South Africa : a phenomenological study on the degree of alignment between stakeholders concerning a sustainable solution to acid mine drainage - Ewart, Timothy Ian (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2011.